2013
DOI: 10.3892/br.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA-related single nucleotide polymorphism of the XPO5 gene is associated with survival of small cell lung cancer patients

Abstract: Abstract. MicroRNA (miRNA)-related single nucleotide polymorphisms (miR-SNPs) in miRNA processing machinery genes affect cancer risk, treatment efficacy and patient prognosis. A miR-SNP of rs11077 located in the 3'UTR of miRNA processing machinery gene XPO5 was examined in small cell lung cancer (SCLC) patients to evaluate its association with cancer survival. A total of 42 patients were enrolled in the present study and genotyped for rs11077 and survival was assessed using the Kaplan-Meier method, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…For example, positive family history is an independent risk for this tumor, and recent studies have identified SNP polymorphisms in individual genes or micro RNAs associated with increased risk for this malignancy. [10][11][12][13][14][15][16] In the present study, we found that VEGF +405G/C SNP polymorphism is associated with risk of lung cancer. Consistent with results of previous clinical and experimental studies, our data also indicated that smoking is a risk factor for lung cancer, with a predilection in males.…”
Section: Discussionmentioning
confidence: 98%
“…For example, positive family history is an independent risk for this tumor, and recent studies have identified SNP polymorphisms in individual genes or micro RNAs associated with increased risk for this malignancy. [10][11][12][13][14][15][16] In the present study, we found that VEGF +405G/C SNP polymorphism is associated with risk of lung cancer. Consistent with results of previous clinical and experimental studies, our data also indicated that smoking is a risk factor for lung cancer, with a predilection in males.…”
Section: Discussionmentioning
confidence: 98%
“…Dysregulation of XPOs associated with subcellular mislocalization of proteins has been reported for various types of human cancer (23). Upregulation of certain XPOs in particular has been associated with cancer progression (24)(25)(26)(27)(28)(29)(30)(31)(32)).…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have indicated that overexpression of XPO5 enhances the activity of miRNAs, and under-or nonexpression of XPO5 results in a decrease in the nuclear output of pre-miRNAs [16,17]. SNPs associated with miRNAs in the XPO5 3′untranslated region (3′UTR) affect the risk of disease in the synthesis pathway of miRNAs [18]. Currently, there is a lack of research on the relationship betweenXPO5 and the risk of NIHL development; however, several studies have demonstrated that the transporter, XPO5, is involved in the miRNA pathway.…”
Section: Introductionmentioning
confidence: 99%